HUMAN CAPITAL DEVELOPMENT AS A FACTOR OF POVERTY REDUCTION - Gafurzhanova Saidakhon Amirtemirkhon kizi (Labor economics and human capital, 2023)
This article explores the issues of poverty reduction based on the development of human capital, in which special attention is paid to the development of the education system, which is an important component of human capital. Also in the article, an analysis of the increase in the coverage of children from 3 to 6 years old by the preschool education system is considered. As the analysis showed, the rate of enrollment of young women in higher education for 2015-2021 improved by 5 times, but compared to the enrollment of men, it is still 4% lower. There is a trend towards an increase in the number of higher educational institutions, including branches of foreign universities and private ones, an increase in state quotas for higher education, as well as the allocation of separate quotas to secondary education graduates with disabilities and from low-income families, which has a positive effect on increasing the coverage of young people with higher education.